THE HARM PRINCIPLE AS A MID-LEVEL PRINCIPLE? THREE PROBLEMS FROM THE CONTEXT OF INFECTIOUS DISEASE CONTROL - Krom, André (Bioethics, 2011)
Effective infectious disease control may require states to restrict the liberty of individuals. Since preventing harm to others is almost universally accepted as a legitimate (prima facie) reason for restricting the liberty of individuals, it seems plausible to employ a mid-level harm principle in infectious disease control. Moral practices like infectious disease control support – or even require – a certain level of theory-modesty. However, employing a mid-level harm principle in infectious disease control faces at least three problems. First, it is unclear what we gain by attaining convergence on a specific formulation of the harm principle. Likely candidates for convergence, a harm principle aimed at preventing harmful conduct, supplemented by considerations of effectiveness and always choosing the least intrusive means still leave ample room for normative disagreement. Second, while mid-level principles are sometimes put forward in response to the problem of normative theories attaching different weight to moral principles, employing a mid-level harm principle completely leaves open how to determine what weight to attach to it in application. Third, there appears to be a trade-off between attaining convergence and finding a formulation of the harm principle that can justify liberty-restrictions in all situations of contagion, including interventions that are commonly allowed. These are not reasons to abandon mid-level theorizing altogether. But there is no reason to be too theory-modest in applied ethics. Morally justifying e.g. if a liberty-restriction in infectious disease control is proportional to the aim of harm-prevention, promptly requires moving beyond the mid-level harm principle.